Global changes and destination management: a systematic approach - Mostafavi Shirazi, Seyedeh Fatemeh; Mat Som, Ahmad Puad (2008)
The increasingly competitive service industry especially in tourism requires a clear understanding of worldwide changes and the systematic approaches for achieving competitive advantages at tourism destinations. A significant factor of a successful tourism destination is the capability of managers in destination to response to universal changes. Based on a review of recent literature, this paper discusses the impacts of global change in tourism industry and the importance of destination management to sustain the competitive advantages of a tourist destination.